Towards a semantic representation of maturity models - Kania, Krzysztof (W kierunku semantycznej reprezentacji modeli dojrzałości, 2011)
Implementing a business process improvement program is a difficult project, which requires large organizational effort and the presence of knowledge. To facilitate this task, we try to support it with IT. This can be achieved by using an approach to business process improvement based on maturity models and converting the original content into a database and knowledge base form. Representing maturity model as a database opens up new possibilities of computer processing of its content. It allows to join maturity models with a diagnostic knowledge base to build an application that will help managers to evaluate and improve the maturity of their business processes. The aim of this paper is to present the possibilities of formal semantic computer representation of maturity models, as a database, and as a knowledge base and to show the benefits of such representation
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics, 2011, Nr 202, s. 37-47
Keywords: semantic representation; maturity model; knowledge base form